Effect of Environmental Attitude and Environmental Awareness Help Green Advertising and Eco-Label to Influence Green Purchasing Behavior of Organic Products - Musdalifah Musdalifah; Debbie Aryani Tribudhi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
The rising concern for environmental sustainability has influenced a shift in societal perspectives, thereby creating demand for businesses to develop organic products as a means of addressing various environmental issues. This study aimed to apply the Theory of Planned Behavior (TPB) to determine the influence of environmental attitude, environmental awareness, green advertising, and eco-labels on green purchasing behavior. Data were collected through a questionnaire survey involving 117 respondents in Jakarta, Indonesia. The empirical findings showed that environmental attitude and eco-labels significantly positively affected green purchasing behavior. While green advertising did not directly affect green purchasing behavior, it significantly influenced environmental attitude and environmental awareness. Environmental awareness did not have a significant direct effect on green purchasing behavior. All supported hypotheses are confirmed.